2020
DOI: 10.1136/bmjopen-2019-033642
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rehabilitation interventions on physical function and immobility-related complications in severe stroke: a systematic review

Abstract: ObjectiveTo evaluate the effectiveness of rehabilitation interventions on physical function and immobility-related complications in severe stroke.DesignSystematic review of electronic databases (Medline, Excerpta Medica database, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Physiotherapy Evidence Database, Database of Research in Stroke, Cochrane Central Register of Controlled Trials) searched between January 1987 and November 2018.MethodsThe Preferred R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 74 publications
(202 reference statements)
0
24
0
2
Order By: Relevance
“…It has been repeatedly reported that neuromuscular electrostimulation (NMES) is a useful tool and gold standard in several rehabilitation procedures [1,2]. Among its most well known benefits are the improvements of muscle strength [3] and neuro-muscular activation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been repeatedly reported that neuromuscular electrostimulation (NMES) is a useful tool and gold standard in several rehabilitation procedures [1,2]. Among its most well known benefits are the improvements of muscle strength [3] and neuro-muscular activation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal effects resulting from NMES, as well as other strategies employed in the fields of rehabilitation and sports medicine, can be measured using infrared thermography (IRT), a precise and noninvasive technology [17]. Analysis of images captured by IRT enables the quantitative measurement of variations in the thermal pattern of surfaces under study, commonly called the "region of interest" (ROI), which are indicators of changes in metabolism, in hemodynamics, or in neuronal thermoregulatory processes [2,18]. Investigations that are based on the combination of thermal images with laser Doppler have postulated that Tsk can be translated into quantity of skin blood flow, so that at higher temperatures, there is greater skin blood flow, and vice versa [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is the largest observational study of active exercise time within physiotherapy sessions. To our knowledge, it is the first study to include patients with severe and very severe strokes, a population who are greatly underrepresented in the literature [36]. Consequently, the inclusion of patients presenting with a range of stroke severity levels increases the generalisability of findings to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, nearly 90% of the stroke survivors reported any form of movement impairments in their upper or lower extremity, which needs professional intervention. Therapeutic methods have shown an effect on improvement in both upper and lower extremities, resulting in improved motor function and hand function [22,23] . Problems like motor function have day-to-day implications in a patient's life in contrast to other impairments like swallowing, thinking, and difficult vision.…”
Section: Discussionmentioning
confidence: 99%